1978
DOI: 10.1148/126.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Aneurysm Formation as a Complication of Interventive Angiography

Abstract: The authors describe a case in which transcatheter embolization was used to treat a large arteriovenous malformation of the scalp (cirsoid aneurysm), with subsequent development of multiple aneurysms at the embolization sites. This previously unreported complication may have far reaching implications in treatment modality selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Angiography is required for the assessment of all collateral links, the presence of an intracranial component, vascular supply of the posterior circulation, venous drainage, and association with sinuses. [ 3 4 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiography is required for the assessment of all collateral links, the presence of an intracranial component, vascular supply of the posterior circulation, venous drainage, and association with sinuses. [ 3 4 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Angiography is required for the assessment of all collateral links, the presence of an intracranial component, vascular supply of the posterior circulation, venous drainage, and association with sinuses. [3,4,13,14] Treatment of scalp AVMs is difficult because of various factors such as the complex vascular anatomy, large collateral links, high-flow rate, and cosmetic factors. The aim of the treatment is complete elimination of the lesion from circulation.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, preoperative embolization of scalp AVM is useful to reduce blood loss during surgical excision. 6,7 Surgical excision is often associated with large skin incisions, skin reconstruction is occasionally necessary, and it may cause facial nerve injury. 2 Therefore, we chose nonsurgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2 Preoperative embolization of a scalp AVM facilitates surgical excision by reducing blood loss. 6,7 Barnwell et al 8 reported patients with scalp AVM who received a combined treatment of injection of a sclerosing material and coil embolization. Here, we report a patient with a scalp AVM who was successfully treated by a combination of transarterial coil embolization and percutaneous thrombin injection for occlusion of the collateral artery.…”
mentioning
confidence: 99%
“…Gelfoam is the material of choice for nonpermanent vascular occlusion. Aneurysm formation at sites of occlusion bas been documented [23]. Gelfoam, prepared in small cores, tailored to catheter luminal diameter, and used in its native state, has been found suitable for occlusion of small bleeding vessels and aneurysms.…”
Section: Embolization Materials and Cathetersmentioning
confidence: 99%